1994
DOI: 10.1002/qua.560520705
|View full text |Cite
|
Sign up to set email alerts
|

Proton release pathway in bacteriorhodopsin: Molecular dynamics and electrostatic calculations

Abstract: We use molecular dynamics, electrostatic, and quantumchemical calculations to discuss chromophore and protein structural changes as well as proton transfer pathways in the first half of the bacteriorhodopsin photocycle. A model for the molecular mechanism is presented, which accounts for the complex pH dependence of the proton release and uptake pattern found for the M intermediates. The results suggest that transient transfer of the Schiff base proton to a nearby tightly bound water molecule is the primary st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
28
0

Year Published

1995
1995
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 62 publications
4
28
0
Order By: Relevance
“…The importance of Arg82 for the proton release mechanism was noted in earlier computational and experimental studies. 39,44 A proton transfer from the SB to Asp85 (p.t. 1), and the release of a proton (p.t.…”
Section: Key Proton Transfer Stepsmentioning
confidence: 99%
“…The importance of Arg82 for the proton release mechanism was noted in earlier computational and experimental studies. 39,44 A proton transfer from the SB to Asp85 (p.t. 1), and the release of a proton (p.t.…”
Section: Key Proton Transfer Stepsmentioning
confidence: 99%
“…XH therefore must be a group close to the surface whose pK a is drastically reduced during the cycle so that under normal conditions the ejection of a proton becomes possible. From calculations of pK changes on the time scale of the L-M transition, it was predicted that the residue E204 might be a candidate for XH (18)(19)(20). Indeed, it could be confirmed that this residue must be involved in the release process since in the mutant E204Q the normal release process is abolished (21).…”
mentioning
confidence: 99%
“…The later part of the photocycle still lies beyond the time window of traditional molecular dynamics theory. Based on the high-resolution structure of bR determined by diffraction experiments, several attempts have been made by using semiempirical or classical force field calculations and the method of simulated annealing to compute the further progression of the photocycle (18)(19)(20)30). Taking into account some known empirical parameters (pK's, Fourier-transformed IR data, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…The results are discussed and related to predictions from molecular dynamics calculations (18)(19)(20).…”
mentioning
confidence: 89%